A falling of the veils: turning points and momentous turning points in leadership and the creation of CSR - Hemingway, Christine A.; Starkey, Kenneth (Springer, 2018)
This article uses the life stories approach to leadership and leadership development. Using exploratory, qualitative data from a Forbes Global 2000 and FTSE 100 company, we discuss the role of the turning point (TP) as an important antecedent of leadership in corporate social responsibility. We argue that TPs are causally efficacious, linking them to the development of life narratives concerned with an evolving sense of personal identity. Using both a multi-disciplinary perspective and a multi-level focus on CSR leadership, we identify four narrative cases. We propose that they helped to re-define individuals’ sense of self and in some extreme cases completely transformed their self-identity as leaders of CSR. Hence we also distinguish the momentous turning point (MTP) that created a seismic shift in personality, through re-evaluation of the individuals’ personal values. We argue that whilst TPs are developmental experiences that can produce responsible leadership, the MTP changes the individuals’ personal priorities in life to produce responsible leadership that perhaps did not exist previously. Thus we appropriate Maslow’s (1976, p. 77) metaphorical phrase ‘A falling of the veils’ from his discussion of peak and desolation experiences that produce personal growth. Using a multi-disciplinary literature from social theory (Archer, 2012) moral psychology (Narvaez, 2009) and social psychology (Schwartz, 2010), we present a theoretical model that illustrates the psychological process of the (M)TP, thus contributing to the growing literature on the microfoundations of CSR.